Modern Challenges of Event Tourism and Business, Organizational Needs - Megi Surmanidze (European Scientific Journal, ESJ, 2023)
Event tourism is one of the growing and high-income directions of the tourism industry, event tourism is characterized by a variety of content, function and purpose, events that are held around the world have a high social, economic, cultural, historical, sports, business industrial significance. The mentioned article analyzes the course of event tourism, its scope and organizational needs and the relevance of event management. The method of literature review  is used for the research. The article discusses the social positive and negative effects of event tourism on the environment, economy and society, as well as the social role in the process of employment and labor market formation. Event management, which is systematically used in event tourism, is new compared to other tourism sectors and is constantly experiencing progress along with the increased demand and need. The research showed that the most important problematic aspect in the process of planning and conducting events is the lack of professional staff and the absence of necessary competencies. Also, the research found that time management is a problem, The respondents have different attitudes towards the digital systems of budgeting, registration and identification of events.